Kierkegaard, pensador post-fundacional - Binetti, María José (ARFIL y UNL, 2019)
Søren Kierkegaard is laid in the History of Philosophy as the thinker of a purely possible freedom, capable of creating its own meaning and actuality. The possible, the virtual, the potency constitute for Kierkegaard the substratum of existence, element, middle and end of its free and creative action. The determination of the infinite possibility as origin and foundation of being supposes the ontological resignification of actuality, in clear contrast with the old metaphysics of the perfect and complete act. The following lines will attempt to read Kierkegaard on the post-foundational horizon of contemporary ontology as a thinker of radical immanence and contingency, whose infinite possibility of power anticipates in many ways the new speculative turn of XXI Century.